Design and implementation of an automatic control system for the regulation and monitoring of the internal conditions of the forced hybrid thermal solar dryer - Molina-Hernández, Pablo José (2022)
For the drying and dehydration of agricultural products, the Instituto Tecnológico de Costa Rica, San Carlos Local Campus has a hybrid forced thermal solar dryer with LP gas backup. The forced system consists of the circulation, by means of turbines, of hot air and hot water through the drying chamber. The hybrid system consists of using solar energy and natural gas to raise the temperature, inside the drying or dehydration chamber. For the humidity control process, the dryer uses a manual system. The disadvantages of the manual humidity control process include (a) reliance on an operator to turn the system on and off, (b) it does not allow adaptation of the system to the environmental conditions around the drying chamber, (c) high energy consumption to reach the humidity conditions required for the storage and processing of agricultural products. The aim was to improve the current dryer by automating the humidity and temperature process. The proposed system uses a PLC (Programmable logic controller) for humidity control, and allows monitoring of humidity and temperature variables, both internal and external to the drying chamber.